VD_FINDINFO Arrêt / 2014 / 776 vom 20. August 2014 - VD Tribunal cantonal (2014)
CURATELLE DE REPRÉSENTATION, CURATEUR, CHOIXEN GÉNÉRAL, REJET DE LA DEMANDE | 394 al. 1 CC, 395 al. 1 CC, 395 al. 3 CC, 401 CC, 403 al. 1 CC, 445 CC, 450 CC